The Analysis of The Characteristics of Leaders in Increasing Human Capacity in The Development of Rural Tourism - Imran, Sarojini; Firmansyah, Riza; Lestari, Kiki K. (Jurnal Penelitian Pariwisata, 2020)
This study aims to analyze the characteristics of community leaders as tourism activists and to analyze the work relationship system between other stakeholder figures. This study used a mixed-method, with interviews community leaders, appropriate informants and questionnaires to 100 local community respondents, who took the case study location in Terong Village. Province of Bangka Belitung Islands. The results showed that there was consistency in the role of leadership in developing the capacity of tourism villages. The leader is the most important aspect besides establishing working relationships with local governments and other stakeholders who bridge the interests of the community or village tourism management business groups and be potential alternative tourism in Tulamben for its good destination image. Keywords: Rural tourism, Leadership, Human capacity.